Process of Evaluation and Attention to Victims of Socio-Political Violence at the National University - Gutiérrez-Gómez, Edgar; Aronés-Cisneros, Angel Alcides; González-Ríos, Rosa Cecilia; Aguilar-Ozejo, Antony; Munaris-Parco, Sonia Beatriz (Journal of Ecohumanism, 2025)
This qualitative ethnographic research work aims to identify and understand the experience of students who access universities through the extraordinary exam, as well as to explore how these institutions implement the processes of care. National universities must attend to the victims of terrorist violence according to Law No. 28592, by virtue of the Report of the Truth and Reconciliation Commission, which covers the period 1982-2000. Through in-depth interviews, participant observation, documentary analysis and triangulation of information, it has become evident that, although the national universities and their authorities formally comply with the Law in their admission processes, in practice there are serious difficulties in its application. These difficulties are associated with the fear of the stigma of “terruqueo” and of being accused of apology for terrorism, which has led to the abandonment of students who enter national universities under the extraordinary modality.